Single cutaneous metastasis due to bladder urothelial carcinoma - Onexy Veranes Velázquez; Rider Aguilar Medina; Isnay Tamayo Blanco (Centro Provincial de Información de Ciencias Médicas, 2016)
The case report of an 85 years old woman is described who was admitted in the Internal Medicine Service of "Dr. Joaquín Castillo Duany" Teaching Clinical Surgical Hospital in Santiago de Cuba due to low back pain, dysuria and hematuria, besides a   6 cm diameter tumor in the abdominal wall, suprapubic region, for 6 months.  The biopsy of the lesion was carried out which results revealed high degree infiltrative urothelial carcinoma, reason why she was transferred to the Urology Service where the exams characteristic of the specialty would be carried out.  The diagnosis was confirmed by means of the cystoscopy and the histopathological analysis.  The treatment was not carried out due to her relatives refusal.